Novel, low-cost bioreactor for in vitro electrical stimulation of cardiac cells - Licata, Joseph P.; Gerstenhaber, Jonathan A.; Lelkes, Peter I. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe successful implantation of laboratory-grown cardiac tissue requires phenotypically mature cardiomyocytes capable of electrophysiological integration with native heart tissue. Pulsed electrical stimulation (ES) has been identified as a promising strategy for enhancing cardiomyocyte maturation. However, there are discrepancies in the literature as to best practices for promoting cardiac differentiation using ES.MethodsThis study presents a novel, 3D printed bioreactor that delivers in vitro ES to human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs), promoting cell maturity and functional readiness for implantation. Finite element analysis and mathematical modeling were used to model the fluid dynamics and to characterize in detail the delivery of pulsatile electrical signals, providing precise control over stimulation parameters such as voltage, current, and charge.ResultsThe bioreactor developed here provides an easy-to-use, inexpensive platform for culturing hiPSC-CMs under the influence of ES and low-shear fluid flow for enhanced nutrient availability, while its “drop-in” design facilitates real-time observation of cultured cells. The electrical stimulation provided is controlled, modeled, and predictable, enabling reproducible experimental conditions and promoting comparability across future studies. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) grown in the bioreactor with ES showed improved differentiation and an enhanced ability to respond to external electrical pacing signals.DiscussionBy offering a standardized platform for ES-based cardiomyocyte maturation, this bioreactor aims to accelerate advancements in cardiac tissue engineering. Future research will explore how variations in ES parameters influence cardiomyocyte phenotype and maturation, contributing to a deeper understanding of cardiac cell development and optimization for therapeutic applications.